DIFUSI INOVASI PROGRAM PEMERINTAH: STUDI KOMUNIKASI PEMBANGUNAN PADA KELOMPOK WANITA TANI ANUGRAH KABUPATEN PADANG PARIAMAN - Safitri, Rany; Asmawi, Asmawi; Arif, Ernita (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
This study aims to determine the process of diffusion of government programs with development communication studies on Anugrah farmer women's groups in Nagari Sungai Buluh Selatan, Batang Anai District, Padang Pariaman District. This research uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation studies. The results of the innovation diffusion research show that the government program is an innovation for the Anugrah farmer women's group. The diffusion process occurs through information dissemination using communication channels, namely correspondence, face to face communication channels, with group meetings and mass media. The duration of the implementation of government programs is not so long, which is around 2 weeks -1 month, and has a positive impact on the social system and the surrounding environment.